Trajectories of personal and professional development of a group of family day carers: learning in the exercise of the profession: Aprender no exercício da profissão - Correia, Isabel; Figueiredo, Irene (Aprender, 2023)
The present study is part of the Programme «Building participatory pedagogies in family day care – capacity building and professional development programme for Childminders and other professionals of early childhood education and care» developed under the auspices of the Aga Khan Foundation Portugal. The study aims to contribute to the understanding of the current situation of Childminders in what concerns the characteristics, potentialities and complexities of their action, as well as to find evidence about the influence of professional development processes, in their professional performance. Information obtained through individual and collective semi-structured interviews (focus group) from Supervisors and Childminders of two-family day-care nurseries in the district of Setúbal is presented. The interpretative analysis of the collected data provide understanding about some identity traits of these professionals, namely the specificity and complexity of their profession, the devalued social image, the precarious working conditions as well as the importance of participation in formal and informal training opportunities in the scope of their professional development. Emphasis is given to valuing the socialization of experiences and knowledge in coherence with each professional and personal course of life, in order to promote and implement high quality education and care contexts for the children and their families.
Keywords: family day care nurseries; supervisors; childminders; early childhood education and care